Peer-reviewed: New method of measuring permanent viscosity loss of polymer-containing lubricants - Holtzinger,J; Green,J; Lamb,G; Atkinson,D; Spikes,H (Tribology and Lubrication Technology, 2012)
An ultrahigh shear rate viscometer (USV) was used to measure the viscosity of polymer solutions. It was found that some polymer solutions in base oil, including those used as engine oil viscosity modifiers, show permanent viscosity loss when subjected to very high shear rates above 106 s-1. The USV was modified to automatically carry out a series of viscosity measurements on the same test lubricant sample. This enabled the accumulation of permanent viscosity loss to be measured over successive strain cycles. As expected, permanent viscosity loss increased with both strain rate and molecular weight. When carried out at 5 × 106 s-1 and 100°C, the test was more severe than the Kurt Orbahn test because samples of lubricants subjected to the latter underwent further shear thinning in the USV. The USV test appears to be a rapid and convenient way to quantify the permanent viscosity loss of polymer-containing lubricants for engine use, and a protocol to assess permanent viscosity loss (PVL) and permanent shear stability index (PSSI) based on viscosity measurements at 106 s-1 before and after shear thinning is outlined. The study also shows that it is important to take into account possible permanent viscosity loss when measuring the viscosity of polymer solutions in veiy high shear rate viscometers such as the USV. This can be done by minimizing the amount of shear to which the lubricant is subjected or by taking successive measurements and subtracting the permanent viscosity loss taking place in each of the first few strain rate cycles.